2010
DOI: 10.3102/0162373709360064
|View full text |Cite
|
Sign up to set email alerts
|

College Graduation Rates for Minority Students in a Selective Technical University: Will Participation in a Summer Bridge Program Contribute to Success?

Abstract: There are many approaches to solving the problem of underrepresentation of some racial and ethnic groups and women in scientific and technical disciplines. Here, the authors evaluate the association of a summer bridge program with the graduation rate of underrepresented minority (URM) students at a selective technical university. They demonstrate that this 5-week program prior to the fall of the 1st year contains elements reported as vital for successful student retention. Using multivariable survival analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 25 publications
(60 reference statements)
1
77
1
Order By: Relevance
“…Similar to the short-format instructional strategies discussed by Gutlerner and Van Vactor (4), much of the available evidence regarding their efficacy relies on self-reported perceptions of value and lacks performance-based or longitudinal assessment (35)(36)(37). However, the few studies that have assessed longer-term outcomes and/or used more rigorous designs find limited, if any, benefits (38,39). Most retention and degree completion results yield null (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the short-format instructional strategies discussed by Gutlerner and Van Vactor (4), much of the available evidence regarding their efficacy relies on self-reported perceptions of value and lacks performance-based or longitudinal assessment (35)(36)(37). However, the few studies that have assessed longer-term outcomes and/or used more rigorous designs find limited, if any, benefits (38,39). Most retention and degree completion results yield null (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…Most retention and degree completion results yield null (e.g., refs. 40 and 41) or small-magnitude effects of limited duration (39,42,43). For instance, Barnett et al (38) reported that the eight programs they studied had small, positive effects on passing math and writing courses in the first semester compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…at NANYANG TECH UNIV LIBRARY on June 11, 2015 abs.sagepub.com Downloaded from one of the most common outcomes studied (Ackerman, 1991;Buck, 1985;Garcia, 1991;Murphy et al, 2010). These studies generally conclude that SBPs help in retaining students.…”
Section: Table 1 (Continued)mentioning
confidence: 82%
“…A few programs publish their successes, but many more go unreported. 7,13,14 Of those that do publish, few maintain control groups, often relying instead on student satisfaction surveys. There is little consensus around the impact of summer bridge programs on student GPAs.…”
Section: Research Backgroundmentioning
confidence: 99%
“…4 Studies show abilities, attitudes, and college-preparation (e.g., AP courses) are main determinants of successful completion of challenging STEM programs. 5,6,7,8 Students from under-resourced schools often have access to less rigorous college-preparation than their peers and subsequently struggle on campus although they possess all of the inherent intelligence necessary to succeed. Additionally, highly selective institutions often fail to take prior preparation into account when designing support programs, assuming that that because admitted students are all academically capable they will each enter college equally prepared to compete.…”
Section: Research Backgroundmentioning
confidence: 99%